KONSELING GIZI TERHADAP PENGETAHUAN, SIKAP DAN TINDAKAN IBU DALAM PERBAIKAN POLA KONSUMSI ANAK AUTISME - Juni Gressilda Louisa Sine; Stefanus Manongga; Intje Picauly (Persagi, 2018)
The prevalence of autism has increased significantly to 1 person with autism per 50 children in the last year compared to 2010 data on the prevalence of autism 1 per 68 children. One of the causes found in children with autism is a disorder of the immune system that underlies the occurrence of food allergies. The immune system is mostly located in the gastrointestinal tract. The purpose of this study was to assess the effectiveness of nutritional counseling on knowledge, attitudes and actions of mothers in improving the consumption patterns of children with autism. The design of this research is quasi experimental study, with sampling technique is consecutive sampling. Based on the inclusion criteria, the mother who is willing to be a sample of 36 mothers of children with autism in Inclusion School and Special School of Kupang City. The analysis used is Paired-Sample t test and Independent-Sample t test. The results showed that mother's knowledge, attitudes and actions about food for autistic children increased significantly between before and after intervention (p <0.05). Mother knowledge, attitudes and actions increase after intervention. Effective nutrition counseling improves the average score of knowledge, attitudes and actions of mothers is high compared with the control group.